Transformations of citizenship: politics of membership in Britain - Silva, Elisabete Mendes (2011)
Dating back from the French revolution, citizenship means a status that confers entitlements and benefits as well as obligations towards the state. Being a citizen is the legal state requirement to become part of the nation. National identity means inclusiveness and identifying oneself with a collective whole. Nonetheless, one can argue that concept has somehow transformed itself in its basic core. What is now the status of citizenship, in a world of gradually more deterritorialised politics? How is citizenship being reconfigured under contemporary conditions? Is postnational cosmopolitan solidarity, so proclaimed nowadays, really possible to attain? As a consequence of the world’s latest terrorist attacks, both in London and in Madrid, European governments are instigating a more controlled defence of the national territory. Therefore, new immigration laws are created within this new social and political context. This paper’s main purpose is to reflect on the politics of membership in Britain and the steps immigrants and ethnic minorities have to take in their journey to citizenship. Special emphasis will thus be put on the law and system of control which governs immigration and asylum in the UK. We will also make reference to the politics of membership carried on in other European countries, such as Portugal, Spain and France, in order to try to understand and compare the theory and practice of citizenship in different European countries.